EKSISTENSI PERAN AYAH DALAM MENYIAPKAN GENERASI MUSLIM YANG SHALEH - Nur Hayani Hayani (STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
Fathers as men have personalities that are generally different from women. The father figure cannot be replaced by the mother. Regardless of whatever mother, he cannot replace the position of a man called a father. Being a good father is one of the normal ideals of a man who has a family. As a good father, father's involvement in a child's life is an absolute necessity. Fathers who are involved and sensitive in childcare will have a positive effect. Her role in the family, interactions with mothers, children and the community will be a model for children in the learning process at every stage of their lives. Father's behavior affect deeply and has positive values ​​that will stay in a child's heart. Similarly, the negative influence will be very easy to decrease to their children. A father figure is needed by a child, in the presence of his children, a father is a determinant stock of piety for children.